Techno-economic analysis and comparison of coal-based chemical technologies with consideration of water resources scarcity - Jinyang Zhao (Elsevier, 2021)
Existing techno-economic analyses of modern coal chemical technologies (MCCTs) neglect water constraints, which may underestimate the production cost of MCCTs and thus mislead investment activities. Considering this background, this study incorporated water scarcity and indirect water cost into a classic techno-economic evaluation model of MCCT. Using this model, our work evaluated and compared the techno-economic indicators with the latest data for four typical MCCTs, including coal-to-liquids (CTL), synthetic natural gas (SNG), coal-to-olefin (CTO), and coal-to-ethylene glycol (CTEG). The results demonstrate the following: 1) The production costs of CTL, SNG, CTO, and CTEG are 5185 CNY/t, 2653 CNY/kNm3, 5918 CNY/t, 4055 CNY/t, respectively. Under the current prices of oil-related products, investment in SNG and CTEG would be risky, investment in CTL should be considered cautiously, and investment in CTO could lead to a profit. 2) Under the current market price of water resources, which does not consider the water constraint of MCCTs, the production cost would be underestimated by at most 12.4% for CTL, 10.6% for SNG, 27.5% for CTO, and 32.4% for CTEG. The sensitivity of the results to some key parameters and investment recommendations considering profitability, capital investment, material consumption, water constraints, and CO2 emissions are also discussed and provided.